Planning Of Solar Power Plant With On-Grid System At The Fourth Building University Of PGRI Semarang - Kusmantoro, Adhi (International Journal of Computer, Network Security and Information System, 2020)
The on-grid system is a system that is used by PLTS directly connected to an existing electricity grid (PLN). Therefore, the on-grid system does not use a battery storage system or supercapacitor. By using this on-grid system, the community has helped the government in reducing PLN's electricity burden. The main objective in this study was to plan an on-grid system using photovoltaics in the four buildings of the University of PGRI Semarang. The research method carried out in the study was collecting data as supporting research including hourly electric load identification data and on-grid system inverter and photovoltaic specifications used, determining the amount of power to be generated in the on-grid system, calculating the number of solar panels will be used, determine the arrangement of solar panels. Based on the load data of Building four, it can be planned to have a capacity of 200 Wp solarland monocrystaline solar panels 166 units of PV modules. In the installation of PV modules there are connected in series or parallel and depending on the size of the on-grid inverter input voltage used. Based on the Sunny Tripower 60 inverter specifications, the inverter input voltage is 685 V to 800 V DC. Based on the calculation of the PV area, a value of 254.19 m2 was obtained. If the strings are arranged then the total power generated by the PV area is 33.15 KWP. The choice of location is based on the consideration that the solar panel faces north with a slope angle of 17.45⁰ and is close to the building installation room.